Understanding pluralistic agriculture extension services through a social governance lens in Northern Uganda - Jawoko, Hannington Odongo; Opio, Alfonse; Mwesigye, Adrian; Bariyo, Rogers (Journal of Agricultural Extension and Rural Development, 2023)
This study analyzed the relationship between smallholder farmers’ perceptions of pluralistic agricultural extension service and social governance. This was aimed at the identification of significant factors that improve social governance practices of local government planning and budgeting process in northern Uganda. Structured interviews with leaders of smallholder farmer associations were conducted. A multinomial logistic regression was performed to test the association of pluralistic agriculture extension services with social governance practices. The results showed that input supply, the management style of extension agents, as well as monitoring and evaluation of smallholder farmers’ activities had a significant and positive influence on the perception of social governance practices. Any negative farmers’ perception of these factors weakens the power relations and the legitimacy of the local government planning and budgeting process. The predictor factors could adequately explain less than 50% change in social governance practices. Nonetheless, we developed a model that clearly depicts the need for local governments to adequately focus their plans and resource allocation
Keywords: Agricultural extension systems; Governance; Legitimacy; Multi-stakeholder platform; National agricultural advisory services; Planning; Power relations; Smallholder farmer